El humor como vestíbulo del clímax trágico en un relato de Julio Ramón Ribeyro - Vila Osores, Belén (2018)
Analyzes an episode clownish in the Diegesis of a tale Lima titled While the Candle Burns, by Julio Ramón Ribeyro. The purpose is to detect a comic incident that works as a vestibular space of tragic climax, in the context of an urban narrative characterized by covering thematic regions such as alienation, resignation, Dislove, drowsiness. The laughter in this episode carries the pain, the comic implies the tragic. To these theoretical budgets is associated the philosophical study on the unlevelness that produces the laughter, and which is approached by Alfred Stern and Henri Bergson. These dialogues make it possible to understand the function of the resource of humour in the text, prior to the tragic moment that will be unleashed in the outcome.